2023
DOI: 10.1182/blood.2022018619
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 acts as a receptor for IL-34 to suppress acute myeloid leukemia in mice

Abstract: The bone marrow microenvironment supports leukocyte mobilization and differentiation and controls the development of leukemias, including acute myeloid leukemia (AML). Here, we found that the development of AML xenotransplants was suppressed in mice with osteoclasts Tsc1 deletion. Tsc1-deficient osteoclasts released a high level of IL-34, which efficiently induced AML cell differentiation and prevented AML progression in various preclinical models. Conversely, AML development was accelerated in IL-34-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is noteworthy that as research on IL-34 advances, additional receptors for IL-34 besides CSF-1R, SDC-1, and PTPRZ1 may be discovered. For instance, TREM2 has recently been identified as an additional receptor for IL-34 [ 17 ]. Exploring the relationship between these novel receptors of IL-34 and poor prognosis in patients with LUAD could enhance our understanding of the role of IL-34 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that as research on IL-34 advances, additional receptors for IL-34 besides CSF-1R, SDC-1, and PTPRZ1 may be discovered. For instance, TREM2 has recently been identified as an additional receptor for IL-34 [ 17 ]. Exploring the relationship between these novel receptors of IL-34 and poor prognosis in patients with LUAD could enhance our understanding of the role of IL-34 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…One caveat regrading this discrepancy would be attributed to the differing binding receptors of CSF1 and IL-34. Although these two ligands can interact with CSF-1R, IL-34 has a lower affinity and correspondingly lower activity than CSF1, moreover, researches have revealed that IL-34 could specifically interact with PTPRZ, 28 SDC1, 57 and TREM2, 58 which may elicit differential signaling cascades and consequences. Collectively, our data revealed that IL-34 exhibited a nonredundant, CSF1-independent role in the progression of cardiac remodeling after IR.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in acute myeloid leukemia (AML), TREM2, as a novel receptor for IL-34, can induce myeloid differentiation and inhibit AML progression by inhibiting the ERK1/2/Rasal3 signaling pathway. On the contrary, TREM2 gene-deficient AML cells and normal myeloid cells exhibit resistance to IL-34 treatment and are associated with poor prognosis ( 59 ). These findings suggest that TREM2 can inhibit tumorigenesis and development by activating different signaling pathways and plays an important tumor suppressor role.…”
Section: Trem2 and Cancermentioning
confidence: 99%